Provenance of Late Triassic Basins during the First Stages of Rifting in Pangea (SW Iberia) - Vilallonga, Filipa (2015)
The Late Triassic basins of SW Portugal were filled with continental detrital deposits dominated by sandstones and some interbedded conglomerates and mudstones. In this study, detrital zircons were separated from samples of the Upper Triassic sandstones of the Silves Formation collected in the Alentejo and Algarve basins. Conventional methods of separation of heavy minerals by sizing, magnetism, and gravity were used, and the zircon grains were dated by U–Pb geochronology using laser ablation–inductively coupled plasma–mass spectrometry (LA–ICP–MS). The analysis of detrital zircon populations using the Kolmogorov–Smirnov statistical test highlights the similarities and differences between samples within the same basin and between the two basins. Samples of both basins have significant similarities with respect to the populations of detrital zircons with ages older than ca. 515 Ma, reflecting their association with the northern Gondwana basement. A comparison of the populations of detrital zircon ages younger than ca. 515 Ma for the two basins shows that: (1) in the Alentejo Basin, Palaeozoic grains reflect the influence of sources related to the upper Palaeozoic formations of the South Portuguese Zone, or the Ossa Morena Zone basement with Variscan (late Palaeozoic) zircon-forming events; and (2) in the Algarve Basin, grains of Palaeozoic age are insignificant, which suggests the Upper Devonian formations of the South Portuguese Zone, or the Ossa Morena Zone basement without Variscan zircon-forming events, as the potential sources.